Acute autoimmune transverse myelitis following COVID-19 vaccination: A case report. Issue 51 (23rd December 2021) - Hirose, Satoshi; Hara, Makoto; Koda, Kento; Natori, Naotoshi; Yokota, Yuki; Ninomiya, Satoko; Nakajima, Hideto
Abstract : Supplemental Digital Content is available in the text Abstract: Rationale: Transverse myelitis is an infectious or noninfectious inflammatory spinal cord syndrome. We report a rare case of transverse myelitis following vaccination against COVID-19. Patient concerns: A 70-year-old male presented with progressive sensorimotor dysfunction of the bilateral lower limbs 7 days after receiving the mRNA-1273 vaccine against COVID-19. Spinal magnetic resonance imaging revealed intramedullary lesions with gadolinium enhancement on the Th1/2 and Th5/6 vertebral levels. Cerebrospinal fluid (CSF) testing showed a mildly increased level of total protein and positive oligoclonal bands (OCB). Diagnosis: The patient was diagnosed with acute transverse myelitis. Intervention: The patient received 5 days of intravenous methylprednisolone pulse (1000 mg/day) followed by oral prednisolone (30 mg/day with gradual tapering). Outcomes: The patient fully recovered from muscle weakness of the lower limbs. He was discharged from our hospital and able to independently walk without unsteadiness. Lesson: This is a rare case of transverse myelitis following COVID-19 vaccination. Positive OCB in CSF in the present case highlights the possibility of autoimmune processes, including polyclonal activation of B lymphocytes, following vaccination.